Intercycle variabilities of basal antral follicle count and ovarian volume in subfertile women and their relationship to reproductive aging: A prospective study - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2005)
Background. Reproducibility is an important issue when using tests for estimating ovarian reserve and counseling patients. However, little is known about the intercycle variabilities of basal antral follicle count and ovarian volume. In this prospective study, we analysed the intercycle variabilities of the antral follicle count and ovarian volume, and compared them with those of other basal ovarian reserve tests in subfertile patients. Method. Fifty-two ovulatory and infertile women were followed for two consecutive spontaneous cycles. The antral follicle Count, ovarian volume, serum follicle stimulating hormone and estradiol levels were determined on day 3 of both cycles. Limits of agreement between two measurements were determined. Results. Limits of agreement were - 6.9 and 6.5 for the antral follicle count, and - 8.3 and 8.6 for the ovarian volume. These degrees of variation corresponded to a range of 1.30 and 1.45 times their means for the ovarian volume and antral follicle count, respectively. The variability in the antral follicle count was greater in women who were younger than 24.5 years than in those who were older. Conclusions. Intercycle variabilities of the antral follicle count and ovarian volume were clinically significant. More variation was observed in the antral follicle count of young infertile patients. Therefore, a low antral follicle count in young, infertile, but ovulatory women should be cautiously interpreted. This may not reflect a low ovarian reserve, and these women may have a high antral follicle count in the next cycle.
Keywords: antral follicle; infertility; intercycle variability; ovarian reserve; ovarian volume; reproducibility; STIMULATING-HORMONE LEVELS; IN-VITRO FERTILIZATION; INFERTILE WOMEN; RESERVE; ULTRASONOGRAPHY; REPRODUCIBILITY; PREDICT; CYCLE; AGE